QS4: Fat Grafting for the Dysesthetic Digit. (July 2021) - Loder, Shawn J.; Kim, Justine S.; Moroni, Elizabeth A.; Peter Rubin, J.; Spiess, Alexander M.
Abstract : Purpose: Digital amputation represents a common injury requiring acute hand surgery intervention. These injuries are often complicated by pain, hypersensitivity, dysesthesia, cold intolerance, and contour deficits/pulp atrophy. Many secondary procedures exist to address these concerns; however, they are often limited by undesirable donor site morbidity and/or complex rehabilitation. There is currently no single gold standard for treatment of the dysesthetic digit. Free adipose transfer via lipofilling offers to correct these defects by providing soft, healthy bulk to the amputated site with minimal comorbidity. Here we describe a protocol and preliminary data for providers considering adipose transfer to the dysesthetic digit. Methods: We examined 113 patients who sustained digit amputations between 2010 and 2019. Patients sustained an average of 1.6+/-0.9 amputations per trauma. 13 patients were identified with chronic pain, dysethesia, cold intolerance, or hypersensitivity that persisted after therapy. Controlling for reversible nail bed pathology, 10 patients demonstrated primary chronic dysesthesia. Results: 4 of 10 patients presenting for chronic amputation stump dysesthesia elected for fat grafting to the fingertip. All patients reported improved pain and reduced dysesthesia/hypersensitivity post-intervention. 3 patients required no further intervention after one round of grafting; 1 patient underwent repeat grafting. Of the non-grafted group, 66.7% (4/6) progressed to revision amputation. There were no operative revision amputations after grafting. Conclusions: Fat grafting to the fingertip offers a simple, safe, and easily accessible technique to augment soft tissue bulk at the digital stump. Our preliminary data suggests that this may be an effective option to manage digital dysesthesia/hyperesthesia.